Penerapan Model Pembelajaran Interaktif untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Kelas V Sekolah Dasar - Astuti, Puri (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The formulation of the research problem is how the learning process, increasing student activity and learning mathematics outcomes through interactive learning models. The research subjects were fifth grade students of SD Negeri Sarireja 01. This research was a classroom action research conducted in 2 cycles. In the first cycle, the average student activity score obtained was 12.9 in the medium category. In cycle II, the average score of student activity was 17.3 in the high category. The increase in student learning outcomes can be seen from the average formative test scores that the researchers gave at the end of each cycle and the percentage of complete learning. In the first cycle, the percentage of students who finished studying was 57.9%. In the second cycle the percentage of students who completed 73.7%. Mastery learning reached 73.7%, exceeding the success indicator, namely learning mastery up to 68%. The conclusion in this study is that the interactive learning model can improve the quality of learning, student activities and learning outcomes of mathematics in the matter of calculating the volume of blocks and triangular prisms.